Understanding Material Safety Data Sheet Language - Frederick M. Fishel (EDIS)
The Hazard Communication Standard requires that chemical manufacturers and importers thoroughly evaluate chemicals. Any chemical that is determined to be hazardous must have a material safety data sheet (MSDS) developed to communicate the hazard potential to users. Their purpose is to provide handlers of chemicals, including pesticides, with the proper procedures for handling and working with the chemical. People who are primary users of a MSDS would include employees who handle a certain material in their daily occupations, those who store chemicals at their place of business, and emergency response crews who need to understand procedures associated should an emergency happen to occur. The MSDS is not designed for someone who may apply a lawn and garden pesticide once or twice a year. They are written in an occupational fashion for those who handle a material routinely. This document is PI-35, one of a series of the Pesticide Information Office, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Published March 2005.